Communication Patterns Toward Children: Study of the Communication Model of Parents and Teachers in School-Age Children Based on the Qur'an Teachings - Abidin, Achmad Anwar (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
This research fills the gap in studies of communication models towards children because, from the existing studies, there is still a space that requires a more profound discussion regarding communication patterns that emphasize the values and spirit of Islamic education from the perspective of the Qur'an. The novelty of the researcher's writing. This research is qualitative. Qualitative research is research that produces descriptive data. The type of qualitative research used in this research is library research. Islamic education for children carried out by parents and teachers in formal, non-formal, and informal education must be equipped with good communication skills. Of course, communication under the Qur'an demanded reliability and promoting dialogue. Parents and teachers must be able to communicate teaching material so that it can be implemented by the child, which in the end, has a positive impact on the child. In everyday life, parents and teachers must be able to communicate well with children because communication is essential. Moreover, in communicating with children according to the guidance of the Qur'an, parents, and teachers should be able to communicate with children with qâulan balighâ, qâulan layyina, qâulan ma'rufa, qâulan maysura, qulan karima and be able to give willingness, advice, preaching and taushiyah so that children become a more polite and moral person like the way of communicating the prophet Ibrahim to the prophet Ismail AS.